The Role of Style Versus Fashion Orientation on Sustainable Apparel Consumption - Gupta, Shipra; Gwozdz, Wencke; Gentry, James (Journal of macromarketing, 2019)
The fashion industry is responsible for bringing some of the worst consumption practices out of individuals by reinforcing tendencies for overconsumption throughout society. Consuming too much has led to negative economic, societal, and environmental consequences. The purpose of this paper is to understand whether promoting a style orientation among consumers (rather than a fashion orientation) will lead to more sustainable apparel consumption. Data collected from 6,386 consumers across five countries that are considered to be leaders in sustainable development (Sweden, Netherlands, Germany, the U.K., and the U.S.) suggest that promoting style can be a potential solution to attain slow fashion and, thus, improve sustainable apparel consumption. We further examine the role of hedonism and materialism in influencing sustainable practices in the industry. Based on the findings, the paper emphasizes the need for the collective effort of different actors, especially the role of government, in creating a more sustainable fashion system.